Fiscal Independence and Effectiveness of Regional Revenue on Human Development Index: A Path Analysis - Wijaya, Erlangga; Tuah, Sunaryo N.; Tiawon, Harin (Institut Bisnis dan Informatika Kesatuan, 2025)
Human development is strongly influenced by regional fiscal capacity, particularly the management of local own-source revenue and fiscal independence. This study examines the direct and indirect effects of local own-source revenue and fiscal independence on the human development index. This study employs a quantitative method, using secondary data on local own-source revenue, fiscal ratios, and human development index indicators, and applies path analysis to estimate the relationships among the variables. Results show that local own-source revenue significantly and positively affects fiscal independence (β = 0.68), which in turn has a strong positive effect on the human development index (β = 0.52). Local own-source revenue also exerts a direct effect on the human development index (β = 0.32), yielding a total effect of 0.674 through fiscal independence. These findings underscore the strategic role of locally generated revenue and fiscal autonomy in promoting human development. Strengthening the management of local own-source revenue and enhancing fiscal governance can reduce reliance on intergovernmental transfers and accelerate inclusive development.